A decision support model for prototyping in-plant milk-run traffic systems - Bocewicz, Grzegorz; Nielsen, Izabela; Zbigniew, Banaszak (IFAC-PapersOnLine, 2019)
In the present study, a declarative model is developed which allows to formulate a constraint satisfaction problem that provides decision support for prototyping in-plant milk-run traffic systems. In particular, the model is used to determine the number of transport trips and their organization in time and space needed for timely delivery of material to specific loading/unloading points. Implemented in a constraints programming driven solver, it allows to formulate forward and reverse milk-run vehicle routing and scheduling problems subject to constraints imposed by an in-plant distribution network. In this context, our contribution can be seen as an alternative approach to DSS design, which allows one to search for solutions by alternate and iterative formulation of successive forward and reverse decision problems.